FIGHTING CARTELS: AN APPLICATION OF ECONOMIC THEORY AND THE EFFECTS OF LENIENCY POLICIES - Klimašauskienė, Danguolė; Giedraitis, Vincentas (Ekonomika, 2011)
The paper focuses on the theory and practice of antitrust action in detecting and deterring cartels and analyzing the development of the modern leniency policy. Drawing from game theory and following the examination of the main conditions and reasons for cartel formation and sustainability and a statistical analysis of cartel prosecutions, our attempt is to show that leniency programs, accompanied by strong enforcement powers and effective sanctions, increase the inherent instability of cartels and therefore have proven to represent a functional and successful tool for detecting and punishing, as well as preventing the formation of anticompetitive agreements.